Women educators, leaders and activists : educational lives and networks 1900-1960 - Fitzgerald, Tanya, 1960-; Smyth, Elizabeth M. (Elizabeth Marian), 1954- (New York : Palgrave Macmillan, 2014)
"The chapters in this edited collection train the intellectual spotlight on women educators to trace the contours of their professional lives and the extent to which they challenged the gendered terrain they occupied. The emphasis is on women's historical public voices and their own interpretation of their 'selves' and 'lives' in their struggle to exercise authority in education at a particular historical moment and in a particular culture. Framing each of the women educators as agents of their own lives emphasizes their individual consciousness and ability to act within their own professional sphere. Thus, women need to be viewed in terms of the historical context in which they lived and the social positions they occupied"--
Machine generated contents note: -- 1. Introduction: Educational Lives and Networks; Tanya Fitzgerald and Elizabeth Smyth2. Networks of Influence: Home Scientists at the University of New Zealand 1911-1941; Tanya Fitzgerald3. Worlds within Worlds: Canadian Women Religious, International Connections, Ecclesiastical Webs and the Secular State; Elizabeth Smyth4. Courting Equality: Catholic Women and Agency in the Reconfiguration of University Education in Ireland; Judith Harford5. Mana Wahine: Boundaries and Connections in the Career of a Maori Educational Leader Bessie (Wene) Te Wenerau Grace (Sister Eudora CSC); Kay Morris Matthews6. Performing Reforming and the Category of Age: Empire, Internationalism and Transnationalism in the Career of Reta Oldham, Headmistress; Joyce Goodman and Zoe Milsom7. Mary Gutteridge (1887-1962): Transnational Careering in the Field of Early Childhood Education; Kay Whitehead8. Henrietta Rodman and the Fight to Further Women's Economic Autonomy; Patricia A. Carter9. Lives, Networks and Topographies of Time and Place: New Turns in the History of Women and Education; Deirdre Raftery.
Includes bibliographical references (p. 190-207) and index.
Keywords: Women in education -- History -- 20th century